IMPLEMENTASI PROGRAM PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA (PKK) BIDANG KESEHATAN DI KECAMATAN MANDAU KABUPATEN BENGKALIS TAHUN 2023 - Alpriani, Osi; ', Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The government plays a role in providing support and coordination to the Family Welfare Empowerment Team (PKK) to ensure the implementation of effective and sustainable family welfare programs. This research aims to describe the Implementation of the Family Welfare Empowerment Program (PKK) in Mandau District in 2023. Research methods This method uses qualitative methods with Grounded Research type research. The types of data used in this research are primary data and secondary data, primary data in the form of data and information originating from primary sources and research informants, and secondary data in the form of documents obtained from related documents. The research location was carried out in Mandau District. Data collection techniques in this research are interview and documentation techniques. Implementation of the Family Welfare Empowerment Program is seen from the compatibility between the Program and the Users, the compatibility between the Program and the Implementing Organization, and the compatibility between the Benefit Group and the Implementing Organization. The findings in this research are that people can take part in all PKK programs regardless of age and several other characteristics, fulfilling their needs for information and education regarding health, nutrition and healthy lifestyles. Fulfilling the needs of several groups, such as pregnant women, toddlers and the elderly, then in the implementing organizational aspect, TP PKK can carry out implementation in various ways, namely identifying problems, setting goals, establishing strategies, then carrying out implementation, seeing community involvement and participation, then see adaptation and evaluation. Keywords: Implementation, Welfare, Organization, Program, Benefits Introduction